Collaborative Governance in Realizing The Medical Tourism Program in Siak District - Benny Chairuddin; Sujianto Sujianto; Harapan Tua RFS; Adianto Adianto (International Journal of Economics Development Research (IJEDR), 2023)
Siak Regency has great potential to develop the medical tourism sector as an effort to diversify the economy and improve health services. This research aims to explore the concept of Collaborative Governance as an effective approach to realizing the medical tourism program in Siak District. The research method used is a literature study, by analyzing various sources related to Collaborative Governance and its implementation in the context of medical tourism. The results of the analysis show that Collaborative Governance can be a relevant and effective framework in facilitating cooperation between the government, the private sector, and the community in the development of medical tourism programs. This collaboration allows for resource synergy, improved accessibility of health services, and the development of supportive tourism infrastructure. The implications of these findings can serve as a foundation for local governments, the private sector, and the community to actively participate in the process of developing a medical tourism program. By utilizing the principles of Collaborative Governance, it is hoped that Siak Regency can achieve sustainability in developing the medical tourism sector as an integral part of efforts to diversify the economy and improve community welfare.